2015
DOI: 10.1016/j.egypro.2015.07.071
|View full text |Cite
|
Sign up to set email alerts
|

Design of 4-terminal Solar Modules Combining Thin-film Wide-Bandgap Top Cells and c-Si Bottom Cells

Abstract: Optical simulations of 4-terminal hybrid tandem modules combining high-efficiency crystalline silicon (c-Si) cells with three different thin-film top cells respectively are presented. We considered three types of thin film PV cells: 1. Enlarged-bandgap oxygenated amorphous silicon (a-SiO:H) cells, 2. Wide-bandgap chalcopyrite (CuGaSe 2 ) cells, and 3. Perovskite (CH 3 NH 3 PbI 3 ) cells. A methodology for evaluating the efficiency gain of the 4-terminal hybrid tandem module is proposed and used to show how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…With the incorporation of PEDOT into the device stack as the HTL, the simulation results deliver a J sc of 19.65 mA cm −2 with respect to the perovskite layer thickness of 300 nm. A similar simulation study has been previously reported by Zhang et al employing Spiro‐OMeTAD as the HTL into the perovskite device stack . The optical losses incurred in the respective layers of the PSC stacks incorporating PEDOT and Spiro‐OMeTAD as HTL, respectively, are also simulated in this work, and shown in Figures S4 and S5 (Supporting Information), respectively.…”
Section: J–v Parameters Of the Best Perovskite Devices With And Withosupporting
confidence: 72%
See 1 more Smart Citation
“…With the incorporation of PEDOT into the device stack as the HTL, the simulation results deliver a J sc of 19.65 mA cm −2 with respect to the perovskite layer thickness of 300 nm. A similar simulation study has been previously reported by Zhang et al employing Spiro‐OMeTAD as the HTL into the perovskite device stack . The optical losses incurred in the respective layers of the PSC stacks incorporating PEDOT and Spiro‐OMeTAD as HTL, respectively, are also simulated in this work, and shown in Figures S4 and S5 (Supporting Information), respectively.…”
Section: J–v Parameters Of the Best Perovskite Devices With And Withosupporting
confidence: 72%
“…The optical properties of the isolated PEDOT films are characterized via ultraviolet‐visible‐near‐infrared (UV–Vis–NIR) spectroscopy and shown in Figure S3 (Supporting Information). The wavelength‐dependent optical constants are adopted from previous works assuming that these do not vary sensitively with respect to the nature of the interfaces. The refractive indices of the layers in the PSC do not diverge much, leading to a low reflection loss.…”
Section: J–v Parameters Of the Best Perovskite Devices With And Withomentioning
confidence: 99%
“…There is a limitation in the voltage for tandem operation, but this drawback is compensated by the advantages of parallel connection [18]. These results are consistent with theoretical or experimental values reported in literature for other types of tandem cells [5,7,8,37]. Figure 4 shows the dependence of the maximum output power density on temperature for the thickness of active layers from Table 3 and for the following parameter values of (11) [26].…”
Section: Resultssupporting
confidence: 80%
“…For example, these high-mobility TCOs have played a key role in achieving the record conversion efficiencies for silicon heterojunction (SHJ) solar cells 8,9 , and are also being explored for CIGS [10][11][12] and perovskite tandem cells. 13,14,15 Among these high-mobility TCOs, In2O3:H is capable of achieving the highest mobility with values even up to 138 cm 2 /Vs. 7 This material was originally developed by Koida et al, using reactive magnetron sputtering at room temperature from an In2O3 target with the addition of H2O vapour, which resulted in mostly amorphous In2O3:H films.…”
Section: Introductionmentioning
confidence: 99%